(untitled) (Research, Society and Development, 2022)
The Amazon has great potential when looking at the context of Sustainability. Much of this propensity for Sustainable Development comes from the large portion of biodiversity that comprises this Amazonian space. In this sense, the need for scientific research aimed at sustainable exploitation of Amazonian natural resources ends up being perceptible. This structured review aimed to analyze data from scientific articles to answer the question “What is the scenario of bioprospecting in the Amazon Context?”. The PICo technique was applied to organize the search strings, snowballing to search for secondary studies and Strauss’s Grounded Theory to analyze the results and inductive theory generation within a time frame of 10 years, between 2010 and 2020. The results of this Review indicate a scenario, apparently, still little explored in relation to the theme Bioprospection in the Amazon, as well as the Bioprospection of Amazonian Fungi. There is a challenging scenario and a perception that issues involving the theme "sustainability" are not widespread among the interdisciplinarities of the areas that make up Environmental Sciences.